Improving Students’ English Vocabulary Using “Guessing Meaning From Context” Strategy - Kurniawan, Iwan (Universitas Islam Negeri Raden Intan Lampung, 2019)
The study aims to improve the students’ vocabulary at MTs Muhammad Daud of Pesawaran, Lampung, using Guessing Meaning from Context strategy. The study employs a classroom action research (CAR) method conducted in three cycles, coupled with a pretest and a posttest. The finding indicates that there is an increase in the students’ vocabulary after the treatment